Conocimientos de las enfermeras y calidad del cuidado al recién nacido Trujillo - Rubio Carranza, Nancy (2015)
This is a quantitative, applied, correlational and cross-sectional research conducted by nurses from the maternal and child area of the Peruvian Clinic and Sanchez Ferrer in Trujillo, during the months of October 2013 to February 2014, in order to determine the relationship between the level of knowledge of nurses and the quality of care during the post-partum period of the newborn in the neonatal service. The sample consisted of 30 nurses as inclusion criteria. Two instruments were used: The Likert scale to assess the quality of nursing care during the post partum period, and a test to assess the level of knowledge of nurses in the post partum period. The results were presented in graphs and statistical tables of single and double entry. The results were statistically analyzed using Fisher's exact test with the following results: 23% of nurses have inadequate knowledge level, 3% have inadequate level of quality of care, the remaining 20% have appropriate quality of care. 77% of nurses have appropriate level of knowledge, 14% have inadequate level of quality of care and 63% have adequate level of quality; concluding that there is insufficient evidence to say that there is relationship between the variables